The Analysis of Interpersonal Metafunction of Anne Hathaway's Speech on International Women's Day 2026 - Izzatul Jannah; Sherly Aisyia Anggraeni; Yohannes Rikki F Situmeang; Widhiyanto Widhiyanto; Galuh Kirana Dwi Areni (Jurnal Pendidikan Edutama, 2026)
This study investigates the realization of interpersonal metafunction in Anne Hathaway’s speech on International Women’s Day 2026 by employing the Systemic Functional Linguistics (SFL) framework. The analysis concentrates on the interpersonal resources embedded in the speech, particularly mood types, speech functions, subject choices, and modality, to examine how linguistic elements are utilized to establish relationships with the audience and convey persuasive messages. The findings demonstrate that declarative clauses are the most frequently occurring mood type and primarily function as statements, indicating that Hathaway’s main objective is to inform, persuade, and raise awareness about issues concerning gender equality and women’s rights. The speech also features several rhetorical questions that encourage audience reflection and emotional involvement rather than seeking direct responses. Furthermore, the recurring use of the inclusive pronoun we reflects an intentional strategy to foster solidarity, collective identity, and shared responsibility among participants. The use of modal verbs, including must, can, will, and would, further reveals the speaker’s attitudes toward obligation, possibility, commitment, and hope for future social progress. These interpersonal linguistic features enable Hathaway to strengthen her connection with the audience, enhance the persuasive impact of her message, and promote collective engagement in addressing gender-related challenges. therefore, the study highlights how interpersonal metafunction serves as an effective linguistic resource for constructing social relationships, influencing audience perspectives, and supporting advocacy for women’s empowerment and gender equality.